AB1005 BULLOUS LUPUS (BSLE) AS THE FIRST MANIFESTATION OF SYSTEMIC LUPUS ERYTHEMATOSUS IN THE PEDIATRIC POPULATION (PSLE): A DIAGNOSTIC CHALLENGE IN DAILY PRACTICE. (13th June 2020) - Torres, F.; Velasquez, M.; Ramirez, L.; Leon, L.; Martinez, M.
Abstract : Background: Cutaneous manifestations are observed in 59–85% of patients with SLE but less than 5% developed BSLE. In the GLADEL cohort, the prevalence is 0.41%. BSLE literature in children is scarce Objectives: to describe the clinical characteristics of the patients with BSLE Methods: series of cases between 2010-2019 of two reference centers. The cases met Camisa and Grimwood criteria for BSLE Results: 5 cases had bullous lesions that resolved with residual hypopigmentation. One case had focal seizure and other patient had arthritis with leukopenia and thrombocytopenia. 2 patients had proteinuria <500 mg/24 hours. There were no cases of lupus nephritis. The median SLEDAI-2K score was 12 (IR: 8-17). All had ANAs in titers greater than 1:160 and four had anti-DNA (+). 5 patients had anti-RNP and 4 had anti-Sm. One case had anti-Ro/anti-La. All presented low C3 and 80% had low C4. 80% had ESR ≥20 mm/hour and CRP greater than 0.5 mg/dl in 60%. All presented clinical response with glucocorticoids and dapsone; one patient had methemoglobinemia that improved. At 3 months, the blisters did not recur in 4 patients except one case that presented relapse due to inadherence. Histologically, the most common finding was subepidermal blisters with neutrophils in the papilar dermis. DIF showed linear deposits of Igs and complement in 4 cases and granular deposits in one case; IgG/IgM were in 5 of the samples. IgA was positive in 60% and C3 in 80% Conclusion: In this series, BSLE was associated with neuropsychiatric, joint and haematological involvement in 40% of patients, without lupus nephritis. Such abnormalities had a parallel course to skin involvement, without recurrences. BSLE tends to have a single-phase behavior and in children unlike adults, severe renal involvement is uncommon References: [1]Pons-Estel GJ, et al. Lupus 2018; 27(10): 1753-1754 Disclosure of Interests: None declared